Development of very low frequency data acquisition system using Raspberry Pi - Gunawan, Teddy Surya; Rahman, Syed Nasibur; Kartiwi, Mira; Ihsanto, Eko (IEEE, 2020)
Space studying has become one of the most informative and popular areas of the new era. Monitoring the space and studying its phenomena was started a long way back. To make the study cheaper and more portable, the Stanford SOLAR Center first presented with a Space Weather Monitoring program called the sudden ionospheric monitors (SID). This monitoring system was used to monitor the Earth’s ionosphere changes, which affected the very low frequency (VLF) radio propagations. This low cost but sensitive detection system is used all around the globe via various modifications. This paper presents the monitoring system’s design and implementation using Raspberry Pi for a smaller and compact base with less power usage and higher sensitivity. Raspberry Pi will be used as the base platform connected to a loop antenna and preamplifier. The acquisition system was written in a Python platform and ran through a Linux system. As a result, an efficient and more portable VLF data acquisition system to detect sudden ionospheric disturbance using Raspberry Pi has been developed. The developed version was able to detect a monitor frequency transmitted from NWC-Australia (19.8kHz), Australia, and VTX3-India (18.2 kHz).